(untitled) (Global Journals of Research in Engineering, 2011)
In this paper the effect of a parallel metal oxide surge arrester on the ferroresonance oscillations of transformers is studied. It is proved that ferroresonance phenomenon in transforemer can be classified in chaotic dynamics systems. In this contribution chaos occurs in system from a sequence of period doubling bifurcation (PDB). Analysis of dynamics of ferroresonant circuit is carried out using bifurcation theory. It is expected that the arresters generally cause ferroresonance drop out. Simulation has been done on a three phase power transformer with one open phase. Effect of varying input voltage is studied. The simulation results reveal that connecting the arrester to transformers poles, exhibits a great mitigating effect on ferroresonant over voltages. Phase plane along with bifurcation diagrams are also presented. Significant effect on the onset of chaos, the range of parameter values that may lead to chaos and magnitude of ferroresonant voltages is obtained, shown and tabulated.